Two positive tuberculosis cases in the late Nigrovits family, 18th century, Vác, Hungary. (June 2015) - Szikossy, Ildikó; Pálfi, György; Molnár, Erika; Karlinger, Kinga; Kovács, Balázs K.; Korom, Csaba; Schultz, Michael; Schmidt-Schultz, Tyede H.; Spigelman, Mark; Donoghue, Helen D.; Kustár, Ágnes; Pap, Ildikó
Summary: Two mummies of the Hungarian mummy collection from Vác were the subjects of anthropological, paleopathological, radiological, paleomicrobiological, paleohistological and paleoproteomic studies. Both individuals belonged to the same family. The father, József Nigrovits (No 29), died at the age of 55 on the 11th of November 1793; his son, Antal Nigrovits (No 54), died on the 16th of July 1803, at the age of 22. They lived in the 18th century in Vác, a small town in northern Hungary. The macroscopic examination of the son showed a severely deformed neck and back region; the father has no visible mark of any illnesses. As earlier researches showed that tuberculosis was widespread in the community, the etiology of these deformities was examined. The paleomicrobiological results found that both individuals were infected with tuberculosis. Although they suffered from TB, the CT scan data of the bodies and their 3D reconstructions showed no skeletal evidence of tuberculosis. The deformity of the son turned to be a developmental abnormality of unknown origin, but no Pott's gibbus was present.